2004
DOI: 10.1007/s00425-004-1404-5
|View full text |Cite
|
Sign up to set email alerts
|

(Z)-3-Hexenol induces defense genes and downstream metabolites in maize

Abstract: In response to insect feeding, corn plants (Zea mays cv. Delprim) release elevated levels of volatile organic compounds (VOCs), including the C(6)-volatile (Z)-3-hexenol. The level of mRNA accumulation for a series of defense genes was monitored in response to application of (Z)-3-hexenol (50 nmol) to undamaged plants. The induction of transcripts for hpl (hydroperoxide lyase), fps (farnesyl pyrophosphate synthase), pal (phenylalanine ammonia-lyase), lox (lipoxygenase), igl (indole-3-glycerol phosphate lyase) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
125
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(134 citation statements)
references
References 50 publications
5
125
1
3
Order By: Relevance
“…In our system there was no effect (Table 2) whilst on tobacco and potato this compound negatively affected the fertility of two Myzus species (Hildebrand et al 1993;Vancanneyt et al 2001). The mobility, in terms of plant uptake, and the specificity of the induction of defence genes, have been reported for cis-hexen-1-ol both in model (lima bean) and crop (maize) plants (Arimura et al 2001;Farag et al 2005) and this makes it an ideal candidate for alternative methods of pest control.…”
Section: Discussionmentioning
confidence: 57%
“…In our system there was no effect (Table 2) whilst on tobacco and potato this compound negatively affected the fertility of two Myzus species (Hildebrand et al 1993;Vancanneyt et al 2001). The mobility, in terms of plant uptake, and the specificity of the induction of defence genes, have been reported for cis-hexen-1-ol both in model (lima bean) and crop (maize) plants (Arimura et al 2001;Farag et al 2005) and this makes it an ideal candidate for alternative methods of pest control.…”
Section: Discussionmentioning
confidence: 57%
“…Which VOCs, then, were responsible for the responses that we observed? Green-leaf volatiles have repeatedly been reported to be active in airborne induction of herbivore resistance (Engelberth et al, 2004;Farag et al, 2005;Ruther and Kleier, 2005;Mirabella et al, 2008), and they can also enhance a plant's direct resistance to certain pathogens, particularly necrotrophic fungi (Kishimoto et al, 2005;Matsui, 2006;Shiojiri et al, 2006). Certain volatiles even might be involved in the resistance of plants to abiotic stress (Behnke et al, 2007), and BTH treatment has been reported to enhance the attractiveness of herbivore-damaged corn seedlings to parasitic wasps (Rostás and Turlings, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Downstream, at the level of prenyltransferases that precede the action of terpene synthases, little is known about regulation of gene expression. FPP synthase, required for sesquiterpene biosynthesis, is upregulated by pathogens in Korean red pepper and cotton (Gossypium hirsutum) (Liu et al 1999) and by insect herbivores in maize (Zea mays) (Farag et al 2005). GGPP synthase is induced in taxus cell suspensions by methyl jasmonate (Hefner et al 1998) and by spider mite-herbivory in tomato .…”
Section: Introductionmentioning
confidence: 99%